Growth and martensitic transformation of ferromagnetic Co-Cr-Ga-Si epitaxial films - Yuru Ge; Klara Lünser; Fabian Ganss; Peter Gaal; Lukas Fink; Sebastian Fähler (Science and Technology of Advanced Materials, 2023)
ABSTRACTDuring cooling, conventional martensitic transformation can only be realized from austenite to martensite. Recently, a so-called reentrant martensitic transformation attracted much interest due to an additional transformation from martensite to austenite during further cooling. Obviously, materials with this reentrant transformation will increase the number of physical effects and possible applications. However, until now, only bulk samples have been available, which are not suitable for applications in micro-devices. In this work, we focus on the Co-Cr-Ga-Si system and examine the suitability of this system for the growth of thin films. We observed that the films grow epitaxially on MgO (100) substrates and exhibit a martensitic transformation if deposited at a sufficiently high temperature or with an additional heat treatment. Films within the austenite state are ferromagnetic while films within the martensitic state just exhibit a very low ferromagnetic order.